CD169 Defines Activated CD14+ Monocytes With Enhanced CD8+ T Cell Activation Capacity - Affandi, Alsya J.; Olesek, Katarzyna; Grabowska, Joanna; Nijen Twilhaar, Maarten K.; Rodríguez, Ernesto; Saris, Anno; Zwart, Eline S.; Nossent, Esther J.; Kalay, Hakan; de Kok, Michael; Kazemier, Geert; Stöckl, Johannes; et al. (Frontiers in Immunology, 2021)
Monocytes are antigen-presenting cells (APCs) that play diverse roles in promoting or regulating inflammatory responses, but their role in T cell stimulation is not well defined. In inflammatory conditions monocytes frequently show increased expression of CD169/Siglec-1, a type-I interferon (IFN-I)-regulated protein. However, little is known about the phenotype and function of these CD169+ monocytes. Here, we have investigated the phenotype of human CD169+ monocytes in different diseases, their capacity to activate CD8+ T cells, and the potential for a targeted-vaccination approach. Using spectral flow cytometry, we detected CD169 expression by CD14+ CD16- classical and CD14+ CD16+ intermediate monocytes and unbiased analysis showed that they were distinct from dendritic cells, including the recently described CD14-expressing DC3. CD169+ monocytes expressed higher expression of co-stimulatory and HLA molecules, suggesting an increased activation state. IFNα treatment highly upregulated CD169 expression on CD14+ monocytes and boosted their capacity to cross-present antigen to CD8+ T cells. Furthermore, we observed CD169+ monocytes in virally-infected patients, including in the blood and bronchoalveolar lavage fluid of COVID-19 patients, as well as in the blood of patients with different types of cancers. Finally, we evaluated two CD169-targeting nanovaccine platforms, antibody- or liposome-based, and we showed that CD169+ monocytes efficiently presented tumor-associated peptides gp100 and WT1 to antigen-specific CD8+ T cells. In conclusion, our data indicate that CD169+ monocytes are activated monocytes with enhanced CD8+ T cell stimulatory capacity and that they emerge as an interesting target in nanovaccine strategies, because of their presence in health and different diseases.